2019
DOI: 10.13189/ujer.2019.071617
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of Brain-Based Learning (BBL) and Intrapersonal Intelligence in Junior High School Mathematics Learning

Abstract: The purpose of this study is to describe junior high school mathematics learning activities and describe the suitability of the Brain-Based Learning (BBL) learning strategy which focuses on intrapersonal intelligence in junior high school mathematics learning. The research is descriptive and qualitative. The data were collected through documentation studies, observations, and interviews with teachers and students. Teachers and students of junior high school SMP Assahil Lampung Timur Indonesia were involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…For example, in Jordan At-Taraweh et al (2021) use of such an approach improved students' achievement in mathematics. This finding was repeated in Indonesia and other countries (Wijayanti et al, 2021;Riskiningtyas & Wangid, 2019;Priatna, 2017;Kartikaningtyas, V., Kusmayadi, T.A., & Riyadi, R., 2018;Noureen, G., Awan, R. N., & Fatima, H., 2017;Mastoni, E., Sumantri, M. S., & Ibrahim, N., 2019). This situation is similar to studies on the effectiveness of brain-based learning in physics; Saleh and Subramaniam (2019), Saleh (2012aSaleh ( , 2012bSaleh ( , 2012c and Sani et al (2019a) all found a positive effect of using BBL to improve students' performance in the subject.…”
Section: Paper | 75supporting
confidence: 82%
“…For example, in Jordan At-Taraweh et al (2021) use of such an approach improved students' achievement in mathematics. This finding was repeated in Indonesia and other countries (Wijayanti et al, 2021;Riskiningtyas & Wangid, 2019;Priatna, 2017;Kartikaningtyas, V., Kusmayadi, T.A., & Riyadi, R., 2018;Noureen, G., Awan, R. N., & Fatima, H., 2017;Mastoni, E., Sumantri, M. S., & Ibrahim, N., 2019). This situation is similar to studies on the effectiveness of brain-based learning in physics; Saleh and Subramaniam (2019), Saleh (2012aSaleh ( , 2012bSaleh ( , 2012c and Sani et al (2019a) all found a positive effect of using BBL to improve students' performance in the subject.…”
Section: Paper | 75supporting
confidence: 82%
“…A number of researchers have conducted investigations on the effect of BBT strategy on science students' achievement in secondary schools. While many of these studies have focussed on secondary school mathematics (Al-Tarawneh, Altarawneh & Karaki, 2021;Kartikaningtyas, Kusmayadi & Riyadi, 2018;Mastoni, Sumantri & Ibrahim, 2019;Mekarina & Ningsih, 2017;Noureen, Awan & Fatima, 2017;Priatna, 2017;Riskiningtyas & Wangid, 2019;Triana, Zubainur & Bahrun, 2019), others have focussed on finding the effect of BBT strategy on biology and chemistry secondary school students' achievement (Alanazi, 2020;Shabatat & Al-Tarawneh, 2016;Akyurek & Afacan, 2013;Varghese & Pandya, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are interesting findings in the application of the seven stages, namely, the use of mind maps, playing music, and implementing brain exercises (Husna et al, 2018;Riskiningtyas & Wangid, 2019;Sani et al, 2019;Suarsana et al, 2017;Yulian & Hayati, 2019;Zaqiah et al, 2022). Besides, there are learning modifications by utilizing animated videos (Winarti & Haq, 2013;Wulansari & Suarni, 2020;Yulian & Hayati, 2019), puzzle media (Mastoni et al, 2019), outdoor activities (Wahyudi & Widodo, 2020), and mini-games (Yudha et al, 2020). This suggests that Brainbased Learning seeks to create a learning environment that has a variety of alternatives.…”
Section: Figure 1 Article Selection Flowmentioning
confidence: 99%
“…Author Result (Aulia et al, 2021;Jazuli et al, 2019;Juniarti et al, 2022;Kartikaningtyas et al, 2017;Kusumaningrum et al, 2021;Mastoni et al, 2019;Mekarina & Ningsih, 2017;Sari Rahmatin & Suyanto, 2019;Wahyudi & Widodo, 2020;Widiana et al, 2017;Winarti & Haq, 2013;Wulansari & Suarni, 2020) Improving student learning outcomes. (Herliandry et al, 2018;Karolina, 2018;Susanti et al, 2019;Wiantara et al, 2020;Zaqiah et al, 2022) Improve critical thinking skills.…”
Section: Table 3 Benefits Of Implementing Brain-based Learning In Ind...unclassified